Stemmer Obrist, Gabriele (2014). Schule führen. Wie Schulleiterinnen und Schulleiter erfolgreich sein und woran sie scheitern können. - Kohlstock, Barbara (Swiss Journal of Educational Research, 2018)
Rezension